Conservation and behavior of Africa's "Big Five". Issue 4 (1st August 2014) - Caro, Tim; Riggio, Jason
Abstract: We examine the conservation status of Africa's "Big Five": lion, leopard, buffalo, black and white rhinoceros and elephant, and the role of behavioral knowledge in their conservation. Efforts to conserve these flagship species consist of in situ conservation, captive breeding and reintroductions. With a few exceptions, we find limited evidence that knowledge of behavior informs conservation programs targeted at these species. For management in the wild, knowledge of infanticide and ranging can provide guidelines for realistic hunting quotas and corridors between protected areas, respectively. For ex situ and reintroduction programs, behavioral knowledge is chiefly focused on improved animal husbandry. Despite a formidable understanding of these species' behavior, the practicalities of using such knowledge may be diminished because exploitation of these species is so forceful and the bulk of efforts aimed at conserving these species (and indeed most other African species) are primarily in situ where behaviorally driven interventions are limited. Our comparative findings suggest that behavior has been of rather narrow use in the conservation of these flagship species [ Current Zoology 60 (4): 486–499, 2014].